Sammlung Etzold - Ein Zeitdokument. - Riese, Hans-Peter; Etzold, Berni; Stachelhaus, Heiner (Mönchengladbach : Städtisches Museum Abteiberg, 1986)
Albrecht, Siegfried ; Alkema, Wobbe ; Arp, Jean ; Becker, Friedrich ; Böhm, Hartmut ; Broodthaers, Marcel ; Castellani, Enrico ; Dorazio, Piero ; Franke, Herbert W. ; Glasmeier, Rolf ; Heerich, Erwin ; Kassák, Lajos ; Kupka, Frank ; Lewitt, Sol ; Mahlmann, Max H. ; etc.
Sammlung Etzold - Ein Zeitdokument, Städtisches Museum Abteiberg, Mönchengladbach, 12. Oktober 1986 bis 20. April 1987
boek